Temperature-mediated invocation of the vacuum state for switchable ultrawide-angle and broadband deflection - Serebryannikov A.E.; Lakhtakia A.; Aalizadeh M.; Ozbay E.; Vandenbosch G.A.E. (My University, 2025)
Temperature-mediated appearance and disappearance of a deflection grating in a diffracting structure is possible by employing InSb as the grating material. InSb transits from the dielectric state to the plasmonic state in the terahertz regime as the temperature increases, this transition being reversible. An intermediate state is the vacuum state in which the real part of the relative permittivity of InSb equals unity while the imaginary part is much smaller. Then the grating virtually disappears, deflection being impossible as only specular reflection can occur. This ON/OFF switching of deflection and relevant angular filtering are realizable over wide ranges of frequency and incidence angle by a temperature change of as low as 20 K. The vacuum state of InSb invoked for ON/OFF switching of deflection and relevant angular filtering can also be obtained for thermally tunable materials other than InSb as well as by using non-thermal mechanisms. © 2018, The Author(s).